Geotechnical engineering state of the art and practice : keynote lectures from GeoCongress 2012 - Rollins, Kyle M.; Zekkos, Dimitrios (American Society of Civil Engineers, 2012)
These keynote lectures were presented at GeoCongress 2012, held in Oakland, California, March 25-29, 2012 and sponsored by the Geo-Institute of ASCE. This book contains 30 peer-reviewed papers that survey the entire breadth of research and practice in geotechnical engineering. Each paper is contributed by distinguished geotechnical engineers who were invited to create a comprehensive overview of the profession by focusing on a specific technical subject. About half the papers present the state of the art by describing current challenges for geotechnical researchers. The other half demonstrates the state of the practice by reporting on issues tackled by geotechnical engineers in the field. Taken together, these papers showcase the best of the profession and form a basis for integrating geotechnical research with its practice. Topics include: foundations and earth stability; geotechnical modeling; site characterization, testing, and monitoring; geoenvironmental engineering; embankments and slope stability; soil properties; pavements; tunneling and underground spaces; and earthquake engineering. This collection is an important touchstone for geotechnical and geoenvironmental engineers, whatever their focus on research and practice. -- Provided by publisher.
Keywords: Engineering geology -- Congresses.; elektronické knihy; electronic books